Effects of Amniotic Fluid Index on Perinatal Outcomes in Preterm Premature Rupture of Membranes [37O]. (May 2017) - Ladella, Subhashini; Leung, Teresa; Cortez, Cynthia
Abstract : INTRODUCTION: Amniotic fluid has antibacterial properties and a protective effect on the fetus. A decrease in amniotic fluid index (AFI) during pregnancy has been associated with increased risk for adverse perinatal outcomes. Prior studies have shown a low AFI of less than 5 cm to be associated with a shorter latency period, however, its association with increased risk of perinatal infection has been unclear. The purpose of this study is to determine if AFI levels in women with preterm premature rupture of membranes (PPROM) are associated with adverse perinatal outcomes. METHODS: A retrospective cross sectional study was performed at Community Regional Medical Center in Fresno, CA on women with diagnosis of PPROM between gestational ages of 23 to 34 weeks during 6/1/2014 to 6/1/2016. The primary predictor variable was AFI level less than 5 cm and greater than 5 cm in relationship to perinatal outcomes. RESULTS: A total of 117 PPROM cases were reviewed, 46 women had an AFI less than 5 cm and 71 women had an AFI greater than 5 cm. Length of stay in NICU was 42 days with AFI less than 5 cm versus 26.5 days with AFI greater than 5 cm (P < .013). CONCLUSION: AFI greater than 5 cm in PPROM is associated with decreased length of stay in the NICU. No significant difference was found between AFI levels and latency period. Further data is needed to increase the power of the study. Research is being done to investigate the association of AFI less than 5 cm with decreased latency period and increased adverse pregnancy outcomes.